Transformasi Pembelajaran Digital di SMK Nurul Jadid: Penerapan Microlearning dalam Perspektif Manajemen Pendidikan Islam - Shulhani, Rahmat (Yayasan Literasi Altruis Khatulistiwa, 2025)
This study aims to explore the implementation of microlearning in enhancing the effectiveness of digital learning at SMK Nurul Jadid, with a focus on the integration of Islamic education values. The method used is a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and documentation to collect data. The results of the study indicate that the implementation of microlearning can increase student engagement in learning, as the material is presented in a concise and easily understandable format. However, the main challenge faced is the limitation of digital infrastructure, such as inadequate devices and unstable internet connections, which affect the accessibility of the material. In addition, although efforts have been made to integrate Islamic education values, there are still shortcomings in incorporating spiritual aspects into the microlearning material. This study recommends improving digital infrastructure, providing further training for teachers, and developing more in-depth material that integrates Islamic education values. Overall, microlearning shows great potential to enhance the effectiveness of digital learning at SMK Nurul Jadid, although further development is needed to address the existing challenges.